The significant influence of having children on the postoperative prognosis of patients with nonsmall cell lung cancer: A propensity score‐matched analysis. (29th May 2018) - Takamori, Shinkichi; Tagawa, Tetsuzo; Toyokawa, Gouji; Ueo, Hiroki; Shimokawa, Mototsugu; Kinoshita, Fumihiko; Matsubara, Taichi; Kozuma, Yuka; Haratake, Naoki; Akamine, Takaki; Katsura, Masakazu; Takada, Kazuki; et al.
Abstract: The aim of this study was to elucidate the relationship between family‐associated factors and the postoperative prognosis in patients with nonsmall cell lung cancer (NSCLC). Additionally, we investigated whether having children was associated with the postoperative maintenance of the nutritional status. We selected 438 NSCLC patients who had undergone curative lung resection between 2004 and 2011 at Kyushu University (Fukuoka, Japan), whose family‐associated factors were available. Nutritional indices, including the prognostic nutritional index (PNI), were used to estimate the change in the nutritional status for 1 year after surgery. A propensity score analysis was conducted after adjusting the following variables: sex, age, smoking history, performance status, pathological stage, and histological type. Three hundred patients (68.5%) had both children and partners. Forty‐nine patients (11.2%) only had children, and 56 (12.8%) patients only had a partner. Thirty‐three patients (7.5%) did not have a partner or children. The overall survival (OS) and disease‐free survival (DFS) of the partner‐present and partner‐absent patients did not differ to a statistically significant extent ( P = .862 and P = .712, respectively). However, childless patients showed significantly shorter OS and DFS in comparison with patients with children ( P = .005 and P = .002, respectively). The postoperative exacerbation of PNI was significantly greater in childless patients than in patients with children ( P = .003). These results remained after propensity score matching. Childless patients had a significantly poorer postoperative prognosis than those with children. Surgeons caring for childless NSCLC patients should be aware of the poorer postoperative outcomes in this population. Abstract : Childless patients had a significantly poorer postoperative prognosis than those with children. Surgeons caring for childless NSCLC patients should be aware of the poorer postoperative outcomes in this population.